2021
DOI: 10.1136/bmjopen-2020-046303
|View full text |Cite
|
Sign up to set email alerts
|

Update on Noma: systematic review on classification, outcomes and follow-up of patients undergoing reconstructive surgery after Noma disease

Abstract: IntroductionNoma is a significant yet neglected disease which affects some of the least developed countries in the world. The long-term benefit and safety of Noma surgical reconstructive missions have recently been under scrutiny due to a perceived lack of measurable outcomes and appropriate follow-up. This study analyses and reports on classifications, outcome measurement tools and follow-up for reconstructive surgery after Noma disease.MethodsThis systematic review was undertaken following Preferred Reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…However, there have been evaluations of noma survivors after surgery which have shown that surgical treatment for noma survivors greatly improves their quality of life, even if functional improvements (specifically mouth opening) are not pronounced [ 14 , 102 , 136 , 141 , 156 ].The extent of long-term sequelae and their impact on quality of life of noma patients depends on the severity of the disease at initial presentation, efficacy of antibiotic treatment, wound debridement and the facial structures affected [ 91 , 92 , 96 , 97 ]. It was noted that a validated, standardized noma patient-reported outcome measurement tool would be helpful in standardizing outcome reporting after surgical treatment [ 136 , 141 , 175 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been evaluations of noma survivors after surgery which have shown that surgical treatment for noma survivors greatly improves their quality of life, even if functional improvements (specifically mouth opening) are not pronounced [ 14 , 102 , 136 , 141 , 156 ].The extent of long-term sequelae and their impact on quality of life of noma patients depends on the severity of the disease at initial presentation, efficacy of antibiotic treatment, wound debridement and the facial structures affected [ 91 , 92 , 96 , 97 ]. It was noted that a validated, standardized noma patient-reported outcome measurement tool would be helpful in standardizing outcome reporting after surgical treatment [ 136 , 141 , 175 ].…”
Section: Resultsmentioning
confidence: 99%
“…The burden of the disease can be explained through its high mortality rate and psychosocial morbidity [14,27]. Noma survivals are often left with devastating orofacial defects [23]. All cases reviewed in this study have reported minor to severe orofacial tissue damages.…”
Section: Discussionmentioning
confidence: 94%
“…Often, those patients that survive are not only severely disfigured, but also rejected from family and society [22]. However, these longer-term effects, including psychosocial aspects, are incompletely understood and an area for further study [23].…”
Section: Introductionmentioning
confidence: 99%
“…Weighted population mean outcomes will then be calculated for prevalence among PSAC. 25 To calculate pooled prevalence estimates (PPE), the inverse variance heterogeneity (IVhet) model 26 in MetaXL will be used for the selected studies, to ensure that statistical error is not underestimated. 24 The level of heterogeneity on selected studies will be evaluated using Cochran's Q and I 2 statistics.…”
Section: Discussionmentioning
confidence: 99%